The Age of Coumarins in Plant–Microbe Interactions - Stringlis, Ioannis A (Plant Cell Physiol, 2019)
Coumarins are a family of plant-derived secondary metabolites that are produced via the phenylpropanoid pathway. In the past decade, coumarins have emerged as iron-mobilizing compounds that are secreted by plant roots and aid in iron uptake from iron-deprived soils. Members of the coumarin family are found in many plant species. Besides their role in iron uptake, coumarins have been extensively studied for their potential to fight infections in both plants and animals. Coumarin activities range from antimicrobial and antiviral to anticoagulant and anticancer. In recent years, studies in the model plant species tobacco and Arabidopsis have significantly increased our understanding of coumarin biosynthesis, accumulation, secretion, chemical modification and their modes of action against plant pathogens. Here, we review current knowledge on coumarins in different plant species. We focus on simple coumarins and provide an overview on their biosynthesis and role in environmental stress responses, with special attention for the recently discovered semiochemical role of coumarins in aboveground and belowground plant–microbe interactions and the assembly of the root microbiome.